Postwar America : a student companion - Sitkoff, Harvard (New York : Oxford University Press, 2000)
Presents articles on people, events, legal cases, social groups and movements, political and social concepts, cultural happenings, and other aspects of life in the United States after World War II.
American Window.
Includes bibliographical references (p. 282-284) and index.
Keywords: United States -- History -- 1945- -- Encyclopedias, Juvenile; United States -- History -- 1945- -- Encyclopedias